PERLINDUNGAN HUKUM BAGI PENYIMPAN UANG DALAM BENTUK DEPOSIT DI BANK (Studi Pada PT. Bank SUMUT KC Kampung Lalang) - Raysa Anjani; jamilah jamilah; aldi Subhan (Universitas Medan Area, 2022)
Legal protection to customers is a very important matter to the depositors’ for their deposits and the bank’s own interests. In the sector’s bank cann not be separated from various kinds of risks thay may arise , such as credit risks and market fluctuation risk and other risks. The research methods is a normative law with analytical descriptive. The research methods are Library Research, namely research conducted based on reading sources, namely laws, books, scientific research, mass media, legal journals related to the material discussed in this thesis.. Field Research is to conduct research directly on the field. In this case, the researchers interviewed PT. SUMUT Bank of branch office Kampung Lalang directly. As is obtained from further research begins qualitatively. The result of the research is about Legal Protection For Money Depositors In The Form Of Bank Deposits is Bank SUMUT periodically conducts a comprehensive review of the management system the company’s risk refers to the applicable regulations, namely, the law authority regulations finance number 18/POJK.03/2016. And Bank SUMUT has a regarding acceptance and identification of prospective customer data and the existence of this standart guide outlines general public policy, , admission procedure, and identification of problems , monitoring, and reporting, employee training.